Eruptions that shook the world - Oppenheimer, Clive (Cambridge University Press, 2011)
"Fire & brimstone: how volcanoes work 'Some volcanos are in a state of incessant eruption; some, on the contrary, remain for centuries in a condition of total outward inertness, and return again to the same state of apparent extinction after a single vivid eruption of short duration; while others exhibit an infinite variety of phases intermediate between the extreme of vivacity and sluggishness.' [1RFA-001] The Earth is cooling down! This has nothing to do with contemporary global warming of the atmosphere and surface. I refer instead to the Earth's interior - the source of the molten rocks erupted by volcanoes throughout the planet's 4.567 billion year history"--